Understanding memristive switching via in situ characterization and device modeling - Wen Sun (Nature Portfolio, 2019)
Memristor as the fourth basic element of electric circuits has drawn substantial attention for developing future computing technologies. Sun et al. report the progress and the challenges facing researchers on understanding memristive switching, and advocate continuous studies using a synergistic approach.